Ethical Issues in News Commercialization: Implications on Journalism Practice in Nigeria - Ngantem, Linus Mun; Dapiya, Kyermun Samuel (Nairobi Journal of Humanities and Social Sciences, 2017)
Ethics and truth in journalism have assumed a global concern as scholars recognize that their basic constituents of objectivity, accuracy, fairness and balance have merely assumed mythical qualities as journalists battle to assign credibility to their news stories. This study was designed to examine ethical issues in news commercialization and its implication on journalism practice in Nigeria. The sanctity of news is gradually being infiltrated by commercial messages of propaganda in the interest of government, private organizations, and elite individuals as distortion of news, imbalanced report, the growing tendency and lack of objectivity are the major problem inherent in journalism practice. The work closely examines the issues involved with a view of fashioning a way forward towards best practices. Anchoring the work are Utilitarianism theory of ethics, Deontology, Virtue ethics, and gate keeping theories which are theories addressing ethical values in news commercialization. The paper concludes that recent journalism practice in Nigeria is plagued with the malaise of news commercialization, and it has negatively affected the image of media institutions in the country. Based on the foregoing, the paper recommends that ethical standard should be raised by practitioners and relevant regulatory agencies should ensure that enforcement of laws and ethics is rigorously pursued to compel media houses to comply with the ethics of the profession in the interest and development of the country Nigeria.